Irrigated Corn Response to Long-Term Nitrogen and Phosphorus Fertilization - A. Schlegel; H. D. Bond (Kansas Agricultural Experiment Station Research Reports, 2017)
Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize the production of irrigated corn in western Kansas. In 2016, N applied alone increased yields by 85 bu/a, whereas P applied alone increased yields by only 12 bu/a. Nitrogen and P applied together increased yields up to 164 bu/a. This is 20 bu/a greater than the 10-year average, where N and P fertilization increased corn yields up to 144 bu/a. Application of 120 lb/a N (with the highest P rate) produced about 94% of maximum yield in 2016, which is similar to the 10-year average. Application of 80 instead of 40 lb P2O5/a increased average yields 6 bu/a. Average grain N content reached a maximum of 0.6 lb/bu, while grain P content reached a maximum of 0.15 lb/ bu (0.34 lb P2O5/bu). At the highest N and P rate, apparent fertilizer nitrogen recovery (grain) (AFNRg) was 44% and apparent fertilizer phosphorus recovery (grain) (AFPRg) was 62%.
Keywords: nitrogen fertilization; phosphorus fertilization; irrigated corn; long-term fertility; nutrient removal